2012
DOI: 10.1016/j.cell.2012.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Contact Chemoreceptors Mediate Male-Male Repulsion and Male-Female Attraction during Drosophila Courtship

Abstract: Summary The elaborate courtship ritual of Drosophila males is dictated by neural circuitry established by the transcription factor Fruitless and triggered by sex-specific sensory cues. Deciphering the role of different stimuli in driving courtship behavior has been limited by the inability to selectively target appropriate sensory classes. Here, we identify two ion channel genes belonging to the degenerin/epithelial sodium channel family, ppk23 and ppk29, which are expressed in fruitless-positive neurons on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
381
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(404 citation statements)
references
References 59 publications
22
381
1
Order By: Relevance
“…A previous Ca 2 þ imaging study 8 demonstrated that the pC1/P1 cluster neurons are activated by female sex pheromones, which stimulate foreleg sensory cells when the male taps the female abdomen 20 . To determine whether the pC1 and pC2l cluster neurons are also active during subsequent courtship bouts maintained by visual stimuli, that is, the presentation of a moving multi-spot pattern, we imaged activity in tethered male flies expressing GCaMP3.0 in dsx-Gal4 positive neurons while they engaged in courtship-like following behaviour on the treadmill ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous Ca 2 þ imaging study 8 demonstrated that the pC1/P1 cluster neurons are activated by female sex pheromones, which stimulate foreleg sensory cells when the male taps the female abdomen 20 . To determine whether the pC1 and pC2l cluster neurons are also active during subsequent courtship bouts maintained by visual stimuli, that is, the presentation of a moving multi-spot pattern, we imaged activity in tethered male flies expressing GCaMP3.0 in dsx-Gal4 positive neurons while they engaged in courtship-like following behaviour on the treadmill ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, at least three members of the TRP channels, TRP1, Painless, and TRPL are expressed in bitter neurons in the labellum where they are involved in detection of aversive compounds (Al-Anzi et al, 2006;Kim et al, 2010;Zhang et al, 2013b). Also, several ppk channels are expressed in taste neurons where they are required for relevant taste modalities such as low-salt detection (Liu et al, 2003b) and intraspecific chemical communication in larvae (Mast et al, 2014), and water perception (Cameron et al, 2010) and chemical communication during courtship in adults Lu et al, 2012;Starostina et al, 2012;Thistle et al, 2012;Toda et al, 2012;Vijayan et al, 2014). Finally, DmXR, a receptor homologous to metabotropic glutamate receptors that has lost the ability to bind glutamate (Mitri et al, 2004), may also act as a taste receptor.…”
Section: Chemoreceptors and Gustatory Detectionmentioning
confidence: 99%
“…Liu et al, 2003aLiu et al, ,b, 2012Lu et al, 2012;Starostina et al, 2012;Thistle et al, 2012;Toda et al, 2012;Zelle et al, 2013;Guo et al, 2014;Mast et al, 2014;Vijayan et al, 2014 Larval terminal organ…”
Section: Olfactory and Gustatory Chemoreceptors In Flies: Several Recmentioning
confidence: 99%
See 1 more Smart Citation
“…Taste is also thought to play a role in mate selection, through the detection of pheromones [1][2][3][4][5] . These important and diverse functions have made the insect taste system a compelling target of investigation into how sensory systems translate environmental cues into relevant behavioral outputs.…”
Section: Introductionmentioning
confidence: 99%